The Influence Of E-Wallet Usage, Financial Literacy And Lifestyle On Financial Management Of Female Civil Servants In Mempawah District - Windi Rati Fritiwi; Dedi Hariyanto; Heni Safitri (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The purpose of this study was to determine the effect of e-wallet usage, financial literacy and lifestyle on financial management of Female Civil Servants in Mempawah Regency. The method used in this research is quantitative method. The population in this study were female civil servants in Mempawah Regency with a total sample of 156 people. The data analysis technique used is multiple linear regression analysis, multiple correlation coefficient (R), coefficient of determination (R2), simultaneous test (F test) and partial test (t test). The results showed a multiple linear regression equation, namely: Y = 4.296 + 0.563 X1 + 0.249 X2 + 0.367 X3. The results of the multiple correlation coefficient show an R value of 0.784, meaning that the variables of e-wallet usage, financial literacy and lifestyle on financial management have a strong relationship. The results of the coefficient of determination R2 show that the contribution of the variables of e-wallet usage, financial literacy and lifestyle in influencing the ups and downs of financial management of Female Civil Servants in Mempawah Regency is 74.7% while the remaining 25.3% is explained by other variables outside the regression model. The results of the simultaneous test (F test) in this study showed an Fcount value of 7.183> 2.66 Ftable. Thus it can be concluded that the use of e-wallets, financial literacy and lifestyle on financial management simultaneously affect the dependent variable, namely financial management. The results of the partial test (t test) on the e-wallet usage variable show a tcount value of 3.811> 1.975 t table, meaning that there is a partially significant influence between the relationship with the use of e-wallets on financial management, while the financial literacy variable shows a tcount value of 2.581> 1.975 t table, meaning that there is a partially significant influence between the relationship with financial literacy on financial management and finally the lifestyle variable shows a tcount value of 3.466> 1.975 t table, meaning that there is a partially significant influence between the relationship with lifestyle on financial management.